Real-time video analysis allows the identification of large vessel occlusion in patients with suspected stroke: feasibility trial of a “telestroke” pathway in Northwestern Switzerland - Thilemann, Sebastian; Traenka, Christoph Kenan; Schaub, Fabian; Nussbaum, Lukas; Bonati, Leo; Peters, Nils; Fladt, Joachim; Nickel, Christian; Hunziker, Patrick; Luethy, Marc; Schädelin, Sabine; Ernst, Axel; et al. (Frontiers in Neurology, 2023)
Background & Aim: Loss of time is a major obstacle for efficient stroke treatment. Our telestroke path intends to optimize prehospital triage using a video link connecting ambulance personnel and a stroke physician. The objectives are: (1st) to identify patients suffering a stroke and (2nd) in particular large vessel occlusion (LVO) strokes, as candidates for endovascular treatment. We have chosen the Rapid Arterial Occlusion Evaluation (RACE) scale for this purpose.Methods: This analysis aims to verify the feasibility of prehospital stroke identification by video assessment. In this prospective telestroke-cohort study we included 97 subjects, in which the RACE-Score (items: facial palsy, arm and leg motor function, head and gaze deviation, aphasia or agnosia) was applied and the assessment videotaped by a trained member of the Emergency Medical Services (EMS) in the field using a mobile device. EachThe recorded patient video was independently assessed by three experienced stroke physicians from a certified stroke center and compared to the neuroimaging gold standard. Within this feasibility study, the stroke code was not altered by the outcome of the RACE assessment and all patients underwent the standard procedures within the emergency unit.Results: We analyzed 97 patients (median age 78 years, 53% female), of whom 51 (52.6%) suffered an acute stroke, 12 (23.5%) of which were due to an LVO and 46 patients had symptoms mimicking a stroke. Sensitivity of stroke identification was 77.8%, specificity was 53.6%. In regards to the identification of an LVO, sensitivity was 69.4% and specificity was 84.3 %. The inter rater agreement in the RACE-Score assessment was ICC = 0.82 (intraclass-correlation coefficient) Conclusion: These results confirm our hypothesis that the local telestroke concept is feasible. It allows correct (i) stroke and (ii) LVO identification in the majority of the cases and thus has the potential to assist in efficient prehospital triage.